Features of tax administration of the largest taxpayers - Darkina Y. A. (Interactive science, 2019)
the relevance of this article is due to the lack of improvement in tax legislation to account for the largest taxpayers, despite the fact that tax revenues account for more than half of all revenues to the budget. At the present stage, the tax administration system should simultaneously ensure: an increase in the level of tax collection, a reduction in the costs of taxpayers, the creation of convenient conditions for the performance of tax payment duties, and observance of the principle of equity. The article discusses the comparison of selection criteria for the largest taxpayers at the federal and regional levels.
Keywords: финансовая система; налоговый учет; налоговое администрирование; налоговая система; tax administration; tax system; financial system; налоговая декларация; крупнейшие налогоплательщики; tax accounting; major taxpayers; tax declaration